Al-Razi on gout - Abd Rahman, Akmal Nurhananie; Shuriye, Abdi Omar (IIUM Press, 2011)
This chapter studies al-Razi's treatese on gout entitled Maqalahfi Ajwa' an-Niqris. The materials used are acquired from the books and academic journals. The study investigates al-Razi's understading on gout, and the main focus of chapter is to enquire answers on how Abu Bakr Muhammad Zakariyya al-Razi treated the desease. Al-Razi's book on gout can be considered as the fIrst authentic, independent work devoted to this desease; in addition, the work has survived to the present day. In view of its medical importance and in crediting al-Razi' s pioneering work on gout, this study has been carried out